A phosphatidylinositol 4, 5-bisphosphate redistribution-based sensing mechanism initiates a phagocytosis programing. Issue 1 (December 2018) - Mu, Libing; Tu, Zhongyuan; Miao, Lin; Ruan, Hefei; Kang, Ning; Hei, Yongzhen; Chen, Jiahuan; Wei, Wei; Gong, Fangling; Wang, Bingjie; Du, Yanan; Ma, Guanghui; et al.
Abstract Phagocytosis is one of the earliest cellular functions, developing approximately 2 billion years ago. Although FcR-based phagocytic signaling is well-studied, how it originated from ancient phagocytosis is unknown. Lipid redistribution upregulates a phagocytic program recapitulating FcR-based phagocytosis with complete dependence on Src family kinases, Syk, and phosphoinositide 3-kinases (PI3K). Here we show that in phagocytes, an atypical ITAM sequence in the ancient membrane anchor protein Moesin transduces signal without receptor activation. Plasma membrane deformation created by solid structure binding generates phosphatidylinositol 4, 5-bisphosphate (PIP2) accumulation at the contact site, which binds the Moesin FERM domain and relocalizes Syk to the membrane via the ITAM motif. Phylogenic analysis traces this signaling using PI3K and Syk to 0.8 billion years ago, earlier than immune receptor signaling. The proposed general model of solid structure phagocytosis implies a preexisting lipid redistribution-based activation platform collecting intracellular signaling components for the emergence of immune receptors. The origin of Fc receptor-based phagocytosis is unknown, although plasma lipid redistribution after solid structure binding induces similar phagocytic signaling. Here, Mu et al. show that PIP2 accumulation from plasma membrane deformation recruits Moesin to trigger receptor-independent phagocytosis.